N-(6-{2-[6-(2,2-Dimethylpropanamido)-2-pyridyl]ethyl}-2-pyridyl)-2,2-dimethylpropanamide - Hoong-Kun Fun; Wan-Sin Loh; Nirmal Kumar Das; Debabrata Sen; Shyamaprosad Goswami (Acta Crystallographica Section E, 2010)
The title compound, C22H30N4O2, lies about a crystallographic inversion center. The whole molecule is disordered over two positions with a refined occupancy ratio of 0.636 (10):0.364 (10). The pyridine rings are approximately planar, with maximum deviations of 0.033 (10) and 0.063 (17) Å for the major and minor components, respectively. The mean planes of the pyridine rings form dihedral angles of 17 (2)° in the major component and 18 (2)° in the minor component with the respective formamide groups attached to them. In the crystal packing, intermolecular N—H...O and C—H...O hydrogen bonds link the molecules into two-dimensional networks parallel to the ab plane.